Biomechanical Evaluation of Dual Plate Configurations for Femoral Shaft Fracture Fixation. (28th April 2019) - El Beaino, Marc; Morris, Randal P.; Lindsey, Ronald W.; Gugala, Zbigniew
Abstract : Aim . This study aimed at comparing the mechanical properties of conventional and locking dual plates in adjacent and orthogonal orientations for the surgical fixation of transverse femoral shaft fractures. It also assessed the failure mechanics after dual adjacent and orthogonal locking plate removal. Methods . Thirty-two composite femurs were transversally osteotomized and randomly assigned for fixation with either dual locking or compression plates in an adjacent or orthogonal configuration. Sixteen specimens were preloaded axially to 20 N and single-leg stance loads were simulated. The remaining sixteen constructs were subjected to torsional loads of 10 Nm at a rate of 10 Nm/s in external and internal rotation of the femoral head in relation to the knee. Overall combined rotational stiffness was calculated. Eight different specimens with no osteotomy underwent the same experiments after dual locked plate removal and were tested to failure in combined eccentric axial and torsional modes. Data were statistically processed using a two-tailed t -test and one-way analysis of variance for the comparison of means between two or more groups, respectively. Results . Orthogonal constructs were statistically stiffer in axial loading compared to their adjacent counterparts in both conventional and locking configurations (p<0.001). Dual locking plates provided higher torsional stiffness than conventional ones within each plate orientation (p<0.01). Neither axial/torsional strength nor failure loads differed between constructs that had adjacent or orthogonal dual locking plates instrumented and then removed (p>0.05). Conclusions . In both orthogonal and adjacent orientations, double locking plates provide higher stability than their dual conventional counterparts. Orthogonal dual plate configuration is more stable and biomechanically superior to dual adjacent plating for constructs fixed with either standard compression or locking plates.